Association of First Trimester Prescription Opioid Use With Congenital Malformations in the Offspring: Population-based Cohort Study. Issue 4 (22nd December 2021) - Bateman, B.T.; Hernandez-Diaz, S.; Straub, L.; Zhu, Y.; Gray, K.J.; Desai, D.J.; Mogun, H.; Gautam, N.; Huybrechts, K.F.
Abstract : ( BMJ . 2021;372:n102) Opioids are commonly prescribed to treat pain during pregnancy, with 5% of pregnant women in Europe, Canada, and Australia receiving opioids for pain. In the United States, 22% women insured through Medicaid are prescribed opioids during pregnancy. Opioids may have a teratogenic effect, but evidence around this topic is limited and unclear. This study aimed to determine the association between prescription opioids in the first trimester and risk of congenital malformations while controlling for confounding factors.